2021
DOI: 10.1016/j.jot.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Medical stretching devices are effective in the treatment of knee arthrofibrosis: A systematic review

Abstract: Aims This systematic review examines the available evidence on the use of medical stretching devices to treat knee arthrofibrosis, it suggests a focus for future studies addressing limitations in current research and identifies gaps in the published literature to facilitate future works. Materials and methods Articles were identified using the Cochrane Library, MEDLINE, PubMed and SCOPUS databases. Articles from peer reviewed journals investigating the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Nonoperative treatment options focus on physical therapy and stretching. 9 , 38 However, these options are often not successful, with physical therapy alone offering just 3° of mean improved motion in one study. 39 For the persistently stiff knee, operative management includes open arthrolysis, arthroscopic lysis of adhesions, and/or a manipulation under anaesthesia (MUA), all with similar levels of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Nonoperative treatment options focus on physical therapy and stretching. 9 , 38 However, these options are often not successful, with physical therapy alone offering just 3° of mean improved motion in one study. 39 For the persistently stiff knee, operative management includes open arthrolysis, arthroscopic lysis of adhesions, and/or a manipulation under anaesthesia (MUA), all with similar levels of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…23 Additionally, the application of continuous passive motion (CPM) has been discussed widely, and many studies have found it to be highly effective in increasing the range of motion of patients with arthrofibrosis. 27 According to one study, patients who used a CPM machine had a significant mean range of motion increase in flexion of 34.6°+ -17°. 27 CPM can be a highly effective option along with the use of physical therapy to help counter the debilitating effects of arthrofibrosis.…”
Section: Physical Therapymentioning
confidence: 99%
“…27 According to one study, patients who used a CPM machine had a significant mean range of motion increase in flexion of 34.6°+ -17°. 27 CPM can be a highly effective option along with the use of physical therapy to help counter the debilitating effects of arthrofibrosis.…”
Section: Physical Therapymentioning
confidence: 99%
“…Surgical interventions may rapidly improve joint ROM but are associated with specific complications [ 3 ]. In addition, surgical trauma can trigger inflammatory reactions, giving rise to even more distinct fibrotic changes [ [4] , [5] , [6] ]. Thus, safe and effective alternative therapeutics are needed to treat this debilitating joint disorder.…”
Section: Introductionmentioning
confidence: 99%